Role of G-Substrate in the NO/cGMP/PKG Signal Transduction Pathway for Photic Entrainment of the Hamster Circadian Clock - Plano, Santiago Andrés (ASN Neuro, 2021)
The mammalian circadian clock at the hypothalamic suprachiasmatic nuclei (SCN) entrains biological rhythms to the 24-h cyclic environment, by encoding light-dark transitions in SCN neurons. Light pulses induce phase shifts in the clock and in circadian rhythms; photic signaling for circadian phase advances involves a nitric oxide (NO)/cyclic guanosine monophosphate (cGMP)/cGMP-dependent protein kinase (PKG) pathway, increasing the expression of Period (Per) genes. Effectors downstream of PKG remain unknown. Here we investigate the role of G-substrate (GS), a PKG substrate, in the hamster SCN. GS and phosphorylated G-substrate (p-GS) were present in a subset of SCN cells. Moreover, GS phosphorylation (p-GS/GS ratio) increased in SCN homogenates after light pulses delivered at circadian time (CT) 18 and intraperitoneal treatment with sildenafil, an inhibitor of phosphodiesterase 5 (a cGMP-specific phosphodiesterase). On the other hand, intracerebroventricular treatment with the PKG inhibitor KT5823, reduced photic phosphorylation of GS to basal levels. Since p-GS could act as a protein phosphatase 2 A (PP2A) inhibitor, we demonstrated physical interaction between p-GS and PP2A in SCN homogenates, and also a light-pulse dependent decrease of PP2A activity. Intracerebroventricular treatment with okadaic acid, a PP2A inhibitor, increased the magnitude of light-induced phase advances of locomotor rhythms. We provide evidence on the physiological phosphorylation of GS as a new downstream effector in the NO/cGMP/PKG photic pathway in the hamster SCN, including its role as a PP2A inhibitor.